Inheritance, or, The vault of souls - Paolini, Christopher (New York : Alfred A. Knopf, 2011)
The young Dragon Rider Eragon must finally confront the evil king Galbatorix to free Alagaesia from his rule once and for all.
Keywords: Dragons -- Fiction; Fantasy fiction